Analisis Tingkat Atribusi Kantor Imigrasi Kelas I Non TPI Karawang dalam Menanggapi Krisis Aplikasi M-Paspor - Arika Sari, Ida Ayu Indira; Mayasari., Mayasari.; Nayiroh, Luluatu (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
There are many things that cause a crisis, one of which is due to product damage. An interesting crisis for product damage is the crisis that occurred at the Non-TPI Karawang Class I Immigration Office in the case of the e-Government Application belonging to the Directorate General of Immigration, namely the M-Paspor Application. The application that was expected to facilitate the passport registration process turned out to cause complaints, especially people who applied for passports. The complaint is caused by the M-Paspor Application which often experiences problems in it. The purpose of this study is to find out at what level the attribution of responsibility to the M-Passport Application crisis that occurred at the Immigration Office Class I Non TPI Karawang seen through Situational Crisis Communication Theory. This theory states that the public has certain attributions regarding the crisis because those attributions will determine the reputation of the institution. Attribution is a public perception of a crisis. In every crisis, of course, it has the potential to threaten the reputation of the institution. The smaller the agency's responsibility for the crisis, the smaller the threat to its reputation, and vice versa. To determine who is responsible for the crisis that occurred, basically grouped into three crisis groups or commonly referred to as crisis clusters. This study uses descriptive qualitative content analysis with observational data collection techniques, interviews and data analysis. Keywords: SCCT, M-Passport, Crisis Cluster